Dichlorodiphenyltrichloroethane exposure and anogenital distance in the Venda Health Examination of Mothers, Babies and their Environment (VHEMBE) birth cohort study, South Africa. (July 2016) - Bornman, M. S.; Chevrier, J.; Rauch, S.; Crause, M.; Obida, M.; Sathyanarayana, S.; Barr, D. B.; Eskenazi, B.
Summary: Dichlorodiphenyltrichloroethane (DDT) is used for malaria control by 10 countries, nine of which are in Africa. Technical DDT contains various isomers with 65–80% insecticidal p, p' ‐DDT and 15–21% o, p′ ‐DDT, an estrogenic chemical, while the persistent metabolite of p, p′ ‐DDT, dichlorodiphenyldichloroethylene ( p, p′ ‐DDE), is an antiandrogen. In utero antiandrogenic exposure reduces anogenital distance in animal models and the anal position index in a single study. This study examined the associations between mother's serum DDT and DDE levels at delivery and anogenital distance in their children at birth and age 1 year. Data were collected as part of the Venda Health Examination of Mothers, Babies and their Environment (VHEMBE), a birth cohort study located in rural South Africa. DDT and DDE concentrations were measured in blood samples collected from 752 mothers at delivery. Anogenital distance measurements, taken at birth ( n  = 671) and age 1 year ( n  = 674), included anofourchette and anoclitoral distances in girls, and anoscrotal and anopenile lengths in boys. We also measured anococcygeal and coccyx‐fourchette distances in girls, while in boys, we measured anococcygeal and coccyx‐scrotal distances as well as penile length and penile width. The anal position index is calculated for both sexes as anoscrotal/coccyx‐scrotal in boys and anofourchette/coccyx‐fourchette in girls. We found no associations between p, p′ ‐DDT/‐DDE or o, p′ ‐DDT and anogenital distance measurements at birth in either boys or girls. At 1 year, o, p′ ‐DDE was negatively associated with anofourchette in girls (β =−1.32 mm, 95% confidence interval (CI) = −2.27, −0.38) and positively associated with penile width in boys (β = 0.30 mm, 95% CI = 0.00, 0.60). The results do not suggest an overt antiandrogenic or estrogenic effect on anogenital distance after long‐term DDT exposure. These weak associations may be due to chance.